Design Android Mobile Learning Application Using Appy Pie on Temperature and Heat Materials - Novita, Maya Sri; Rahmad, M; Syafi’i, Muhammad (Proceedings of the UR International Conference on Educational Sciences, 2018)
This study aims to produce android mobile learning application using appy pie software on temperature and heat materials as a valid physics learning media for senior high school. Research was conducted in Physics Education Laboratory of Riau University. This research is a type of research and development using research design adapted from ADDIE instructional model with Analysis, Design and Develop stage only. Data in this research is validation score from validator with research instrument used is validation quisioner. The data collection technique used is observation by using validation sheet with data analysis technique is descriptive analysis. Each component of android mobile learning applications using appy pie software on temperature and heat material is valid if it has an average score > 2.50 which is in high or very high category. The results of this research indicate that the application of mobile learning